Media Edukasi “Peduli Stunting” Berbasis Website Dalam Peningkatan Pengetahuan dan Keterampilan Kader Kesehatan Wilayah Pinggiran Sungai Kapuas - Masmuri, Masmuri; Hidayah, Nurul; Limansyah, Dodik (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2025)
Stunting has become a global concern, as reflected in worldwide nutrition improvement initiatives. In efforts to detect and prevent stunting, collaboration with various stakeholders is required, one of whom is community health cadres. Cadres need to acquire basic information and technology-based skills to support stunting prevention. This study aimed to examine the effectiveness of website-based educational media on cadres’ knowledge and skills. The research employed a quasi-experimental design with a pre-test post-test control group approach. Total sampling was used, involving 100 respondents divided into two groups, with sessions lasting 45–60 minutes each. Research instruments included questionnaires assessing cadres’ knowledge and skills related to stunting prevention. The results, analyzed using the marginal homogeneity test, showed a p-value of 0.000 (p < 0.05), indicating the effectiveness of website-based educational media in improving cadres’ knowledge and skills regarding early detection of stunting compared to the control group that used leaflet media. Website-based educational media proved effective in enhancing cadres’ knowledge and skills in early stunting detection, including identifying child growth curves and developmental milestones according to age. This study recommends cross-sectoral collaboration to improve internet access, provide continuous cadre assistance, and integrate digital educational media into community health programs to optimize stunting prevention.